Preparationof Fe-Chitosan Schiff Base Complex - Boy Chandra Sitanggang; Basuki Wirjosentono; Mimpin Ginting (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract.Chitosan Schiff base (BS) was synthesized through reaction of chitosan with salycilaldehyde, next, chitosan Schiff base (BS) reacted with Fe to form Fe-chitosan Schiff base complex (BSF). The presence of Schiff base confirmed by FT-IR at 1604,77 cm-1 for imine group. Chitosan soluble in acidic solution while chitosan Schiff base partially dissolve. Subsequently, absorption of Fe was determine with ICP-MS at 1, 2, 3, 4, 5 hours (BSF 1, BSF2, BSF 3, BSF 4, BSF 5) resulting 269,98, 289, 311,8, 361,06, 492,51 ppm. Keywords: chitosan, chitosan Schiff base, Fe complex